(untitled) - Swardson, Nick.; Nealon, Kevin; 1953-; 1967-; Barillet, Pierre; Kidman, Nicole; 1967-; Grédy, Jean-Pierre; 1920-2022.; Matthews, Dave; 1999-; Dugan, Dennis; et al. (Culver City, Calif., 2011)
A plastic surgeon who is romancing a much younger schoolteacher enlists his loyal assistant to pretend to be his soon-to-be ex-wife in order to cover up a careless lie. When more lies backfire, the assistants kids become involved, and everyone heads off for a weekend in Hawaii that will change all their lives.
Keywords: Truthfulness and falsehood; Drama; Plastic surgeons; Man-woman relationships; Drama; Drama; Drama; Video recordings for people with visual disabilities; Video recordings for the hearing impaired; Feature films; Films for people with visual disabilities; Fiction films; Comedy films